A prospective cohort study measuring cost-benefit analysis of the Otago Exercise Programme in community dwelling adults with rheumatoid arthritis - Abdulrazaq, Siyar (BMC Health Serv Res, 2018)
BACKGROUND: Falls are one of the major health problems in adults with Rheumatoid Arthritis (RA). Interventions, such as the Otago Exercise Programme (OEP), can reduce falls in community dwelling adults by up to 35%. The cost-benefits of such a programme in adults with RA have not been studied. The aims of this study were to determine the healthcare cost of falls in adults with RA, and estimate whether it may be cost efficient to roll out the OEP to improve function and prevent falls in adults living with RA. METHODS: Patients with Rheumatoid Arthritis aged ≥18 years were recruited from four rheumatology clinics across the Northwest of England. Participants were followed up for 1 year with monthly fall calendars, telephone calls and self-report questionnaires. Estimated medical cost of a fall-related injury incurred per-person were calculated and compared with OEP implementation costs to establish potential economic benefits. RESULTS: Five hundred thirty-five patients were recruited and 598 falls were reported by 195 patients. Cumulative medical costs resulting from all injury leading to hospital services is £374,354 (US$540,485). Average estimated cost per fall is £1120 (US$1617). Estimated cost of implementing the OEP for 535 people is £116,479 (US$168,504) or £217.72 (US$314.34) per-person. Based on effectiveness of the OEP it can be estimated that out of the 598 falls, 209 falls would be prevented. This suggests that £234,583 (US$338,116) savings could be made, a net benefit of £118,104 (US$170,623). CONCLUSIONS: Implementation of the OEP programme for patients with RA has potentially significant economic benefits and should be considered for patients with the condition.